ANTISIPASI DIDAKTIS TERKAIT LEARNING OBSTACLE DALAM PROBLEM SOLVING BANGUN DATAR DENGAN MEMANFAATKAN POTENSI BERPIKIR KREATIF - Rahasima, Rahasima; Suratman, Sugiatno; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research generally aims to clarify and solve learningobstacle in the problem solving of plane figure in SMPN 1 Sungai Kakap with didactic anticipation which utilizescreative thinking potential of students in the plane figure especially related to the base and height of the triangle. Subjects who participated in this study were four students. The method used in this study is the design of a single subject design with A-B-A 'design.The instrument used in the form of a reasoned multiple choice test consisting of pre-test and post-test.Before being given anticipation of didactic by utilizing the potential of creative thinking, the subjects of the study experienced learningobstacle in the problem solving that was known from the pre-test results of the students and through personal interviews conducted. After being given didactic anticipation with creative thinking potential, learningobstacle in the problem solving can be minimized. This is indicated by the reduced learning obstacle in the problem solving experienced by the subject. Thus, the didactic anticipation by utilizing the potential of creative thinking can solve learningobstacle in the problem solving of plane figure.Keywords: Anticipation Didaktis, Learning Obstacle, Problem Solving, Potential of Creative ThinkingÂ